Visualizing the In Vivo Evolution of an Injectable and Thermosensitive Hydrogel Using Tri‐Modal Bioimaging. Issue 9 (18th June 2020) - Chen, Xiaobin; Zhang, Jiulong; Wu, Kaiting; Wu, Xiaohui; Tang, Jingyu; Cui, Shuquan; Cao, Dinglingge; Liu, Ruili; Peng, Chen; Yu, Lin; Ding, Jiandong
Abstract: Degradability of biomaterials brings many opportunities as well as great challenges to their clinical applications. However, reports of systematic in vivo biodegradation are rather limited due to lack of adequate methodology for real‐time observations. Herein, a tri‐modal bioimaging technique is developed, enabling real time monitoring of biodegradation of synthetic polymers in vivo. The demonstrated material is a successful preclinical poly(lactic acid‐ co ‐glycolic acid)‐ b ‐poly(ethylene glycol)‐ b ‐poly(lactic acid‐ co ‐glycolic acid) thermosensitive hydrogel that undergoes a spontaneous sol–gel transition upon heating. A macromolecular fluorescence probe and a contrast agent of magnetic resonance imaging (MRI) are designed and synthesized. After subcutaneous injection of the hydrogel containing the two probes into mice, the degradation behaviors of the material are longitudinally and noninvasively tracked via the collaborative application of ultrasound, fluorescence, and MRI. Integrating the noninvasive imaging with the traditional anatomic observations, a three‐stage degradation mechanism of such a hydrogel is proposed for the first time. Also, the dissolved polymers and degradation products in the body are mainly eliminated via liver, gallbladder, and spleen. This work has great value for promoting the future clinical application of these kind of promising hydrogels. Meanwhile, this technological platform provides beneficial inspiration and methodology to investigate in vivo fate of biomaterials. Abstract : A multi‐modal bioimaging technique is developed to visualize the degradation of biomaterials in vivo. PLGA‐PEG‐PLGA thermosensitive hydrogel is chosen as the demonstrated material. With the help of two imaging probes, the in vivo evolution of the hydrogel is presented in real time via the collaboration application of ultrasound, fluorescence, and MRI, and a three‐stage degradation mechanism is then suggested.